Metropolitan Wordsworth: Allegory as Affirmation and Critique in The Prelude - Allen, Stuart (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
AbstractIn this essay, I contest the view of recent historicist and New Historicist critics that the London books of The Prelude feature a “conservative view” of the city and capitalism. I argue that Wordsworth does not flee the social variety and perceived chaos of London in preference for his bourgeois domestic retreat in Grasmere. However, nor do I suggest that Wordsworth offers a “proto-Marxist” critique of capitalism. Instead, I show that the use of allegory in The Prelude enables Wordsworth not only to convey the alienating character of the city (and the law of the market dominating it), but also to explore London’s affective and imaginative potential. I argue that Wordsworth affirms the city and nature, and that his critique of certain aspects of London cannot be reduced to any ideological position – Burkean or Painite, for example.Drawing on Adorno’s claim that the successful work of art “transcends false consciousness”, I submit that Wordsworth’s commitment to the autonomy of the aesthetic reflects a distinctly undogmatic politics (“Lyric” 214). Embodied solely as art, Wordsworth’s critique balks at any instrumental realisation. Opposing the anti-aesthetic bent of some historicist writers, I argue that Wordsworth’s art is permanently adversarial and does not harden into either a political manifesto or false consciousness. Simultaneously affirmatory and critical, The Prelude is relatively free of ideological prejudice in its exploration of the full diversity of feeling.